Therapeutic Lessons to be Learned From the Role of Complement Regulators as Double-Edged Sword in Health and Disease - de Boer, Esther C. W.; van Mourik, Anouk G.; Jongerius, Ilse (Frontiers in Immunology, 2020)
The complement system is an important part of the innate immune system, providing a strong defense against pathogens and removing apoptotic cells and immune complexes. Due to its strength, it is important that healthy human cells are protected against damage induced by the complement system. To be protected from complement, each cell type relies on a specific combination of both soluble and membrane-bound regulators. Their importance is indicated by the amount of pathologies associated with abnormalities in these complement regulators. Here, will discuss the current knowledge on complement regulatory protein polymorphisms and expression levels together with their link to disease. These diseases often result in red blood cell destruction or occur in the eye, kidney or brain, which are tissues known for aberrant complement activity or regulation. In addition, complement regulators have also been associated with different types of cancer, although their mechanisms here have not been elucidated yet. In most of these pathologies, treatments are limited and do not prevent the complement system from attacking host cells, but rather fight the consequences of the complement-mediated damage, using for example blood transfusions in anemic patients. Currently only few drugs targeting the complement are used in the clinic. With further demand for therapeutics rising linked to the wide range of complement-mediated disease we should broaden our horizon towards treatments that can actually protect the host cells against complement. Here, we will discuss the latest insights on how complement regulators can benefit therapeutics. Such therapeutics are currently being developed extensively, and can be categorized into full-length complement regulators, engineered complement regulators and antibodies targeting complement regulators. In conclusion, this review provides an overview of the complement regulatory proteins and their links to disease, together with their potential in the development of novel therapeutics.